2020
DOI: 10.1177/1077699020940340
|View full text |Cite
|
Sign up to set email alerts
|

Worth to Share? How Content Characteristics and Article Competitiveness Influence News Sharing on Social Network Sites

Abstract: We investigated how sharing performance on Facebook and Twitter is influenced both by news articles’ content characteristics and the availability of additional news articles reporting on the same news topic. We conducted a multi-method study, integrating automated data collection and manual/automated content analyses of 1,764 German online news articles. Our findings show the influence of news factors and, more importantly, news outlets on sharing performance, while simultaneously highlighting differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
1
17
0
4
Order By: Relevance
“…Results confirmed this hypothesis by showing that news routines and formal variables are more relevant to explain news sharing than are content variables. This is in line with previous studies that have demonstrated the strong impact that news outlets characteristics (Karnowski et al, 2020), as well as other aspects of online news routines, like the boosting of videos, and other visual cues produced on news sharing (Bastos, 2015;Boczkowski & Mitchelstein, 2012;Bright, 2016;Salgado & Bobba, 2019). This phenomenon can be traced back to studies that investigated the content characteristics associated with recipients' news selection and information recall from reading newspapers.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Results confirmed this hypothesis by showing that news routines and formal variables are more relevant to explain news sharing than are content variables. This is in line with previous studies that have demonstrated the strong impact that news outlets characteristics (Karnowski et al, 2020), as well as other aspects of online news routines, like the boosting of videos, and other visual cues produced on news sharing (Bastos, 2015;Boczkowski & Mitchelstein, 2012;Bright, 2016;Salgado & Bobba, 2019). This phenomenon can be traced back to studies that investigated the content characteristics associated with recipients' news selection and information recall from reading newspapers.…”
Section: Resultssupporting
confidence: 88%
“…52-53). Bastos (2015), Christin (2015), Kalsnes and Larsson (2018), Karnowski et al (2020) found similar results by analyzing data from different countries.…”
Section: News Sharing and Politics In Facebookmentioning
confidence: 64%
See 2 more Smart Citations
“…Importantly, while more passive users less regularly click the "follow" button for news outlets than more active news consumers (Leonhard et al, 2020), more news could also be included in one's social media feeds because of friends' engagement with news outlets (Boczkowski et al, 2018). Driven by the perceived "shareworthiness" (Karnowski et al, 2021;Trilling et al, 2017) of news items, this diffusion of news via SNS "is a continuous process involving journalists, users, intermediaries, and algorithms" (Brosius et al, 2019, p. 133), which equally affects and is affected by a user's surrounding social network. News on SNS are, thus, brought to one's attention through the "interactive features and affordances of various social media platforms, particularly those which reduce attentional effort" (Oeldorf-Hirsch & Srinivasan, 2021, p. 11).…”
Section: Active and Passive Online News Usementioning
confidence: 99%